13.1k views
2 votes
Hello, can you please express this without denominators with the work?


(a^4b)/(c^2d^3)

Thanks a lot!

1 Answer

3 votes

\bf a^{-{ n}} \implies \cfrac{1}{a^( n)}\qquad \qquad \cfrac{1}{a^( n)}\implies a^{-{ n}} \\ \quad \\ % negative exponential denominator a^{{ n}} \implies \cfrac{1}{a^(- n)} \qquad \qquad \cfrac{1}{a^(- n)}\implies \cfrac{1}{(1)/(a^( n))}\implies a^{{ n}} \\\\ -----------------------------\\\\ \cfrac{a^4b}{c^2d^3}\implies \cfrac{a^4}{1}\cdot \cfrac{b^1}{1}\cdot \cfrac{1}{c^2}\cdot \cfrac{1}{d^3}\implies a^4\cdot b^1\cdot c^(-2)\cdot d^(-3)\implies a^4bc^(-2)d^(-3)
User Justin Du Coeur
by
6.1k points